Partisipasi Politik Masyarakat Kecamatan Jayakerta Pada Pemilihan Kepala Daerah Serentak Kabupaten Karawang Tahun 2020 Di Masa Pandemi Covid 19 - Deri Ramdani Idris; Gili Argenti; Sopyan Resmana Adiarsa (Peneliti.net, 2022)
This study aims to study and determine the Political Participation of the Jayakerta District Community in the 2020 Karawang Regency simultaneous regional head election during the Covid 19 pandemic. This study used a descriptive qualitative research method with data collection methods in the form of interviews, observations and documentation studies. This study uses the theory of political participation proposed by Milbrath with four indicators, namely the presence of political incentives, factors of a person's personal characteristics, factors of a person's social characteristics, and factors of the political situation or environment. The results of this study can be seen from the four factors of Milbrath's political participation. First, political stimulation shows that political stimulation in the 2020 Karawang Regency election in Jayakerta District shows a lack of stimulation, this is due to the lack of socialization carried out by the Jayakerta District PPK. The two factors of a person's personal characteristics indicate that the political awareness of the people of Jayakerta Subdistrict is still low, this can be seen from the lack of people who want to be involved in the Karawang election organizers in 2020. The three factors of a person's social characteristics, in terms of social characteristics in Jayakerta District, money politics are very massive and occur and strongly influence the community to participate. The four factors of the situation or political environment in the 2020 Karawang election, many people in the Jayakerta District were confirmed to have been exposed to the COVID-19 virus, so there were concerns from the public to attend and use their voting rights to the polling station.